2017
DOI: 10.5194/acp-17-7827-2017
|View full text |Cite
|
Sign up to set email alerts
|

Surface-charge-induced orientation of interfacial water suppresses heterogeneous ice nucleation on <i>α</i>-alumina (0001)

Abstract: Surface charge is one of the surface properties of atmospheric aerosols, which has been linked to heterogeneous ice nucleation and hence cloud formation, microphysics, and optical properties. Despite the importance of surface charge for ice nucleation, many questions remain on the molecular-level mechanisms at work. Here, we combine droplet-freezing assay studies with vibrational sum frequency generation (SFG) spectroscopy to correlate interfacial water structure to surface nucleation strength. We study immers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 75 publications
7
68
2
1
Order By: Relevance
“…Lovering et al (2017) suggested the presence of a transient stackingdisordered ice at the interfaces during freezing. Abdelmonem et al (2018) have reported that the observed transient signals arise from a smooth transition between water and ice and do not necessarily indicate transient species. It was demonstrated that the transient change in the signal intensity results from an interference between different SFG peak parameters changing at different rates.…”
Section: Transient Freezing and Melting Peaksmentioning
confidence: 98%
See 1 more Smart Citation
“…Lovering et al (2017) suggested the presence of a transient stackingdisordered ice at the interfaces during freezing. Abdelmonem et al (2018) have reported that the observed transient signals arise from a smooth transition between water and ice and do not necessarily indicate transient species. It was demonstrated that the transient change in the signal intensity results from an interference between different SFG peak parameters changing at different rates.…”
Section: Transient Freezing and Melting Peaksmentioning
confidence: 98%
“…Although this study was not aimed at discussing the transient freezing peak, the obtained data force us to reconsider this recently observed ambiguous phenomenon. The transient peak upon freezing was reported at pH 9.8 for the aqueoussolution-mica interface using SFG (sum-frequency generation) spectroscopy (Anim-Danso et al, 2016), for a neutral water-silica interface using SFG spectroscopy (Lovering et al, 2017), for a neutral water-mica and water-sapphire interface using SHG spectroscopy (Abdelmonem, 2017), and for a pH 9 aqueous-solution-sapphire interface using SFG spectroscopy (Abdelmonem et al, 2018). Anim-Danso et al (2016) supposed that the transient signal is due to progressive events occurring near the surface during the phase transition, without specifying a potential process.…”
Section: Transient Freezing and Melting Peaksmentioning
confidence: 99%
“…The SHG experiments were conducted using a femtosecond laser system (Solstice, Spectra Physics) with a fundamental beam of 800 nm wavelength, 3.5 mJ pulse energy, ∼ 80 fs pulse width, 1 kHz repetition rate, and a beam diameter of ∼ 2 mm at the interface. The supercooled SHG setup and the measuring cell are similar to those described in previous publications (Abdelmonem et al, 2015(Abdelmonem et al, , 2017. Compared to the setup described in Abdelmonem et al (2015), a single fundamental beam incident on the interface was used ( Fig.…”
Section: Materials and Setupmentioning
confidence: 99%
“…They have been isolated from decaying leaf litter and can induce freezing at temperatures up to −2 • C (Schnell and Vali, 1972;Maki et al, 1974;Vali et al, 1976;Möhler et al, 2007). P. syringae are gramnegative bacteria that populate leaf surfaces and are able to cause frost injuries in plants (Lindow, 1983;Hirano and Upper, 2000;Akila et al, 2018). They were shown to owe their IN activity to a protein located on the outer cell membrane that templates ice through a sequence of amino acids providing an epitaxial fit to ice (Kajava and Lindow, 1993;Murray et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…IN activity is preserved when the cells are disrupted, though with a shift to lower freezing temperatures (Govindarajan and Lindow, 1988). At lower temperatures, other types of bacteria (including gram-positive ones) also proved to exhibit IN activity (Ponder et al, 2005;Mortazavi et al, 2008;Failor et al, 2017;Akila et al, 2018).…”
Section: Introductionmentioning
confidence: 99%